Menyesuaikan Konsep Web E- Commerce dengan Tujuan dan Model Bisnis yang di Inginkan - Titin Sumarni; Riani Septiana; Syera Syera; Ega Aqil Al Hafizh (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Developing an effective e-commerce web concept requires adjustments to the goals and business model desired by the company. Every business has unique needs, target markets, and strategies that should be reflected in the e-commerce platform design and features. The main focus is how business objectives, such as increasing sales, expanding the market, or strengthening the brand, can be integrated into the technical and aesthetic aspects of the platform. Apart from that, this study also explores user interface (UI) and user experience (UX) design elements, payment system integration, and the use of analytics to support strategic decision making. Adjusting the right e-commerce web concept can increase operational efficiency, customer attraction, and overall business success. The method used in this research is based on a literature study with references from books that discuss Adapting the E-Commerce Web Concept to the desired goals and business model through textbooks, e-books or from open discussions about e-Business on the internet. Discussions about web commerce and matters related to Adapting the E-Commerce Web Concept to Business Goals and Models, such as e-Commerce and others, can be obtained from all kinds of scientific journal literature which has a lot of discussion about the definition of e-commerce.